Imperatives, Direct Address, and the Construction of Ethos in Dale Carnegie’s How to Win Friends and Influence People - Elisabeth Magdalena Atakay (Dinamika Bahasa dan Budaya, 2026)
This study examines how imperative sentences and direct second-person address function as rhetorical strategies in Dale Carnegie’s How to Win Friends and Influence People. Drawing on rhetorical theory—particularly the concept of ethos—the study investigates how these linguistic features engage readers, guide behavior, and establish the author’s credibility. Using a qualitative content-analysis design supported by quantitative data, the study analyzes 141 selected sentences containing imperatives and direct address through the pronouns “you,” “your,” and “yourself.” The results show that imperative sentences are frequently combined with direct address, producing a text that is reader-centered and interactive. Imperatives serve functions such as instruction, advice, encouragement, warning, and moral guidance, providing clear and actionable direction, while direct address engages readers by fostering personal connection, prompting self-reflection, and presenting hypothetical scenarios. Together, these two features substantially contribute to the construction of ethos: imperatives convey wisdom and authority, while direct address fosters empathy and personal connection, jointly portraying Carnegie as a credible, trustworthy, and supportive mentor. The study demonstrates that simple, easily understandable linguistic choices can effectively strengthen persuasive communication in self-help literature. Keywords: Rhetorical strategies; imperatives; direct address; self-help discourse; persuasive language